Romance for the Curious : Why Study Romance?. - Vayda, Michael (The Curious Academic Publishing, 2019)
Are you considering Romance as your major or career? This book, co-authored by over 20 top professors, gives you the ability and confidence to make an informed major/career choice. So, you don't know what you can do with a major in Romance? You don't know why study Romance? You don't know what the research issues and scholarship opportunities are in Romance? You are confused about the career options in Romance? Don't worry. We know choosing a career path is a major decision, but that's why we have co-authored this book to help you. Take this book as an investment in your career. You need help.